Caribbean Cultural Heritage and the Nation Aruba, Bonaire and Curaçao in a Regional Context - van Stipriaan, Alex; Alofs, Luc; Guadeloupe, Francio (Leiden University Press, 2023)
Centuries of intense and involuntary migrations deeply impacted the development of the creolised cultures on the Dutch Caribbean islands of Aruba, Bonaire, and Curaçao. This volume describes various forms of cultural heritage produced on these islands over time and whether these heritages are part of their 'national' identifications. What forms of heritage express the idea of a shared "we" (nation-building) and what images are presented to the outside world (nation-branding)? What cultural heritage is shared between the islands and what are some real or perceived differences? In this book, examples of cultural heritage on these three islands ranging from sports to questions of reparations, from museums to digital humanities, from archaeology to music, from language and literature to tourism, and from visual art to diaspora policies are compared to developments elsewhere in the Caribbean.